Integrating the Spirit of Kakan Dike Arin Sare to Promote Religious Moderation in East Flores, Indonesia - Yosep Belen Keban; Skolastika Lelu (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Living together in different beliefs is sometimes the cause of religious conflicts in Indonesia. These conditions require the attitude of religious moderation as the foundation of living together through local culture or local wisdom. This study aims to describe, explore, and analyze the local wisdom of Lamaholot in the spirit of kakan dike arin sare to build an attitude of religious moderation and make this expression a way to create an attitude of religious moderation in the land of Lamaholot. This qualitative study was carried out in Horinara Village, Adonara Island, East Flores Regency. The implementation of this research was carried out from January-April 2025. The data was obtained through in-depth interviews with six key informants, namely: traditional leaders, religious leaders, and community leaders. In addition, observation and documentation are carried out to collect data and then analyzed using Huberman and Miles' theory, namely through data collection, data reduction, and conclusion drawn. The result of this research is that the spirit of Lamaholot kakan dike arin sare contains educational values that can be used as a guideline to build a peaceful life in different beliefs. The integration of the spirit of kakan dike arin sare is a solution in realizing religious moderation in Horinara Village, East Flores Regency. The contribution of this research is that it can increase community insight, strengthen the concept of religious moderation and can also be implemented in common life in the midst of differences in beliefs in building religious moderation through local wisdom kakan dike arin sare. In addition, this research can also be used as a foundation for the ministry of religion and local governments in integrating cultural practices as a guide to the house of moderation in religion.